2018
DOI: 10.1016/j.jcf.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypoglycemia during oral glucose tolerance testing in adults with cystic fibrosis and risk of developing cystic fibrosis-related diabetes

Abstract: Hypoglycemia following OGTT is common in CF however the 10 year risk of developing CFRD in these patients was low. Males and those who were heterozygous deltaF508 were at higher risk for hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 17 publications
4
21
0
Order By: Relevance
“… 28 It has been suggested that hypoglycemia during OGTT is an early clinical manifestation of Type 2 diabetes, 33 and those who exhibited hypoglycemia in our study tended to have higher glucose and insulin levels during the OGTT. However, a recent large study found that participants with hypoglycemia during an OGTT had slower progression to CFRD and also had better clinical status as defined by lung function 34 . Thus longitudinal monitoring of these participants is needed to determine if moderate and severe hypoglycemia are an early indicator of AGT.…”
Section: Discussionmentioning
confidence: 99%
“… 28 It has been suggested that hypoglycemia during OGTT is an early clinical manifestation of Type 2 diabetes, 33 and those who exhibited hypoglycemia in our study tended to have higher glucose and insulin levels during the OGTT. However, a recent large study found that participants with hypoglycemia during an OGTT had slower progression to CFRD and also had better clinical status as defined by lung function 34 . Thus longitudinal monitoring of these participants is needed to determine if moderate and severe hypoglycemia are an early indicator of AGT.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In those who were hypoglycemic, the probability of remaining CFRD free over the subsequent 10 years, was found to be 86.1%. 27…”
Section: Endocrine Disordersmentioning
confidence: 98%
“…The hallmark of CFRD is elevated blood glucose, but hypoglycemia can also occur during screening tests. Two single center studies evaluating oral glucose tolerance tests (OGTT) found that 15% ‐29.6% of patients had hypoglycemia during OGTT, usually occurring at the 2‐hour glucose measurement . The patients with hypoglycemia were more likely to be older, male, heterozygous for deltaF508, have a higher BMI and be pancreatic sufficient .…”
Section: Multisystem Effects Of Cystic Fibrosismentioning
confidence: 99%
See 2 more Smart Citations